Microbiological profile and epidemiological perspective on urinary tract infections (UTIs) in a tertiary medical center in Western Mexico - Reyes-Martinez, Pedro; Sierra-Diaz, Erick; Ortiz-Lazareno, Pablo Cesar; Garcia-Gutierrez, Mariana; Ramírez-de-Arellano, Adrián; Sandoval-Pinto, Elena; Cremades, Rosa (Frontiers in Microbiology, 2026)
BackgroundUrinary tract infections are among the most frequent healthcare-associated infections and represent a major public health challenge due to their increasing antimicrobial resistance. Data from tertiary-care hospitals in Mexico remain scarce. This study aims to describe prevalence and microbiological profile of healthcare-associated UTIs in a tertiary medical facility in western Mexico.MethodsA cross-sectional study included all UTI cases recorded from January to December 2024. Data was obtained from the institutional epidemiological surveillance platform (INOSO). Descriptive statistics were applied using measures of central tendency, proportions and confidence intervals. Antimicrobial resistance profiles were analyzed using automated Vitek® testing for Antibiotic susceptibility testing and mass spectrometry for pathogen identification.ResultsA total of 376 patients were included (mean age 52.9 years; 53.2% women). Healthcare-associated UTIs represented 80.6% of cases. Monthly incidence displayed a multimodal pattern with peaks in April and October. Nephrology, Cardiology, and Neurosurgery accounted for >50% of cases. Among 120 isolates, bacteria comprised 70.8%, mainly Escherichia coli (35.8%), Klebsiella pneumoniae, and Pseudomonas aeruginosa; fungal isolates (29.2%) were predominantly Candida albicans. Extensive drug resistance was observed in Providencia rettgeri (resistant to all tested antibiotics) and Acinetobacter baumannii.ConclusionUTIs in a tertiary-care hospital in Mexico exhibit high prevalence, multimodal temporal dynamics, and alarming antimicrobial resistance. Continuous surveillance, antimicrobial stewardship, and targeted infection-control strategies are urgently needed in high-risk hospital units.